Brady Bonds and Default Probabilities - Izvorski, Ivailo (IMF Working Papers; Working Paper, 1998)
This paper computes the default probabilities implicit in the prices of Brady bonds of seven developing countries and examines the factors that determine the high cross-correlation of the probability paths. The term structure of U.S. interest rates and the ratio of long-term foreign debt to GDP, together with a developing market index, explain more than 75 percent of the cross-sectional distribution of the default probabilities. The paper also demonstrates a new way to extract sovereign riskiness, implicit in traded bond prices. This allows the above results to be interpreted as explaining the cross-sectional distribution of sovereign riskiness as well.